OUTCOMES OF PREGNANCY, CHILDBIRTH, AND THE POSTPARTUM PERIOD IN YOUNG WOMEN - Светлана Ивановна Елгина; Любовь Андреевна Кондратова (The Publishing House Medicine and Enlightenment, 2021)
Objective - to study the course of pregnancy, the outcomes of childbirth and the postpartum period in young women. Materials and methods. A retrospective analysis of the medical histories of 400 women in the State Medical Institution «Kuzbass Clinical Hospital named after S. V. Belyaev», «Perinatal Center», Kemerovo, for the period from 2015 to 2018 was carried out. The main group included 200 girls under the age of 18, the control group - 200 girls aged 20-25 years. The course of pregnancy, complications of childbirth and the postpartum period were evaluated. The obtained data were processed using the Statistics 6.0 program. The critical level of significance of the differences was estimated as p, equal to or greater than 0.05. Results. It was found that young primiparous women were somatically healthier than girls in the group of favorable reproductive age. The most frequent complications of pregnancy were gestational anemia and pyelonephritis, less often early toxicosis, gestacin diabetes mellitus and the threat of termination of pregnancy. In minors, compared with 20-25-year-old women in labor, preterm labor, induced, operative labor by emergency caesarean section and benefits in childbirth are more common, and birth injuries are less common. There are differences in the indications for planned surgical treatment. Less often, complications of the late postpartum period in the form of subinvolution of the uterus and lochiomyoma. Anthropometric indicators and Apgar score at birth in newborns are the same. Conclusion. The course of pregnancy, childbirth and the postpartum period in young people has its own characteristics. Premature, induced, and operative births were more common in young women. However, in the young, the late postpartum period was more favorable. There were no differences in the outcome of labor for the fetus.